Is Hyperopia an Important Risk Factor for PACG in the Dutch Population?—A Case Control Study - Saskia H. M. van Romunde; Gijs Thepass; Hans G. Lemij (Journal of Ophthalmology)
Objectives. To determine if hyperopia is a risk factor for primary angle-closure glaucoma (PACG) in the Dutch population and to identify other biometrical parameters as risk factors for PACG including axial length (AL), anterior chamber depth (ACD), and k values. Methods. The study population consisted of PACG patients that had undergone a laser peripheral iridotomy (LPI). The control group consisted of age- and gender-matched cataract patients. The main outcome was hyperopia (spherical equivalent ≥+0.5 dioptres) measured with IOL Master or autorefractor. Refractive error, ACD, AL, and k values were tested with a Mann-Whitney U test and by logistic regression. Results. 117 PACG patients and 234 controls were included (mean age = 80 years ± 3.6). The prevalence of hyperopia in patients and controls was 69.6% and 61.1%, respectively (Fisher’s test P=0.076). Mann-Whitney U test showed no statistically significant relation with refractive error (P=0.068) or k values (P=0.607). In contrast, ACD and AL were statistically significant (P<0.001). Tested with logistic regression, only ACD was a significant predictor of PACG (P<0.001). Conclusion. There was no statistically significant correlation between refractive error and PACG. ACD was strongly correlated, though, with PACG, whereas AL turned out to be a less significant risk factor.